Pendampingan Pendidikan dalam Penerapan Metode Average Untuk Perhitungan Barang Habis Pakai Pada SMK Budi Agung Medan - Hartono Hartono; Nur Azelina Harahap; Rohima Rohima (Jurnal Pengabdian Masyarakat Berbasis Teknologi, 2021)
This average method assumes that any change in inventory, either due to purchases or sales by the company, will immediately get the average value of the remaining inventory. The average value of the remaining goods is obtained by dividing the total value of the remaining inventory by the number of units of the relevant goods. For data recording activities of company consumables. Microsoft Office Excel 2003 is still used, although only used to create input reports manually, these financial statements are still used. limited to LT (annual report), so the possibility of errors in accounting records is very high. The company's source of funds comes from the company's operating profits. Visual Basic comes from the BASIC language developed in 1963. BASIC stands for all-purpose symbol instruction code for beginners. As the name suggests, the purpose of making the BASIC language is to make it easier for users to learn, create and develop computer programs. Visual Basic is a further development of the BASIC language by Microsoft. Visual Basic is designed to be used as a tool to create and develop programs quickly (Rapid Application Development: RAD), especially if you use a windows-based interface (Graphical User Interface: GUI). UML (Unified Modeling Language) is a powerful tool in the field of object-oriented systems development. This is because UML provides a visual modeling language that allows system developers to create blueprints for their vision in a standard form that is easy to understand, and is equipped with an effective mechanism for sharing and communicating their designs with others. UML is built on a 4 + 1 view model. This model is based on the fact that the structure of a system is described in 5 views, one of which is the use case view. SQL Server is a Relational Database Management System (RDBMS) which is used to store data. The data stored in the database can be small or large. With SQL Server 2005, this is not a problem because SQL Server 2005 has resources capable of managing data